PENGARUH BAURAN PEMASARAN TERHADAP LOYALITAS PELANGGAN PRODUK PT.COCA-COLA DI CABANG CIMAHI - Helmut Martahi Saoloan Tambunan; Rosmegawati (Jurnal Manajemen FE-UB, 2022)
Abstract The purpose of this study was to study the effect of the marketing mix on customer loyalty to PT.COCA-COLA Cimahi (CCBI) products. While the method used in this research is descriptive analysis, multiple linear regression analysis, and correlation coefficient. Marketing mix at PT. Coca-Cola Cimahi branch (CCBI) is implemented through four sub-variables namely product, price, distribution and promotion which have a fairly good performance according to customer ratings, although the price variable is not significant but has a very small effect, this means that the price variable will not make a huge difference. From the calculation results it is known that the majority of customer loyalty levels are at the Client level, namely customers who are not affected by other products offered by other companies with a proportion of 27%. to other products by 26%, creating prospects carried out by respondents in 9 Coca-cola products by 40%, in making purchases outside the product line by 29%. Judging from the calculations, it can be interpreted that the marketing mix variables have different influences, both direct and indirect influences. The magnitude of these influences is as follows: The product variable gives a direct effect of at most 7.8% with an indirect effect of giving a value of 13.1%. Keywords: Marketing Mix and Customer Loyalty